2009
DOI: 10.2147/btt.s5619
|View full text |Cite
|
Sign up to set email alerts
|

Finding a new drug and vaccine for emerging swine flu: What is the concept?

Abstract: Influenza is a well known infection of the respiratory system. The main clinical manifestations of influenza include fever, sore throat, headache, cough, coryza, and malaise. Apart from the well known classical influenza, there are also groups of influenza virus infections that are called "atypical infection". These infections are usually due to a novel influenza virus infection. In early 2009, an emerging novel influenza originating from Mexico called swine flu was reported. The World Health Organization note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…6,7 Continuous infections, up to several thousand cases, since its first emerging in April 2009 confirm the seriousness of the problem. It is also no doubt that there is no country that succeeds in getting rid of or completely controlling the infection.…”
Section: Why We Need Swine Flu Vaccine?mentioning
confidence: 98%
See 1 more Smart Citation
“…6,7 Continuous infections, up to several thousand cases, since its first emerging in April 2009 confirm the seriousness of the problem. It is also no doubt that there is no country that succeeds in getting rid of or completely controlling the infection.…”
Section: Why We Need Swine Flu Vaccine?mentioning
confidence: 98%
“…In addition, there is evidence that some elders have already circulating protective immunity to swine flu. 6,7 Of interest, this might imply that there might be an emerging of swine flu in the previous days, many decades ago when there is no available molecular technique to sequence the exact viral sequence, and the elder ones who have protective immunity might be the survivors from that outbreak. 8 Nevertheless, most of the populations in the world have no protective immunity to swine flu.…”
Section: Protective Immunity To Swine Flumentioning
confidence: 99%
“…In addition, based on the pandemic mode of development, the complete data on vaccine study cannot be expected and postmarketing surveillance is strongly recommended. [17] Nevertheless, it is believed that the new swine flu vaccine is similarly effective and safe.…”
Section: Efficacy and Adverse Effect Of Swine Flu Vaccination In Oncomentioning
confidence: 99%
“…The reports indicated that the 1918 H1N1 pandemic caused the death of 20-50 million people worldwide and current H1N1 pandemic is feared of resulting into the similar effect [5]. The World Health Organization (WHO) announced the level 6 precaution, the highest precaution level, for the 2009 infl uenza pandemic [6]. It was discovered that the new H1N1 strain evolved as a result of strong purifying selection, widely different from the strains that are reported during recent past few years, but surprisingly it is closely related to the ancient strain reported in 1918 [7].…”
Section: Introductionmentioning
confidence: 99%